Distribution of the critical and other points in boundary problems with nonlocal boundary condition - Pečiulytė, Sigita; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2007)
In this paper the Sturm–Liouville problem with one classical and other nonlocal two-point or integral boundary condition is investigated. There are critical points of the characteristic function analysed. We investigate how distribution of the critical points depends on nonlocal boundary condition parameters.